Smart Reading: Pelatihan Bedah Jurnal Sistem Informasi Berbasis Speed Reading pada Mahasiswa S1 Institut Bakti Nusantara - Winia Waziana; Dita Novita Sari; Erliza Septia Nagara (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Academic literacy demands require undergraduate students to efficiently digest scientific articles. However, many Information Systems students at Institut Bakti Nusantara experience literacy fatigue and spend 2–3 hours understanding a single journal due to rigid, word-by-word reading methods and difficulty decoding technical components like system architectures and algorithms. This community service (PkM) implements the